Reports of Judgments, Advisory Opinions and Orders 2020: Appeal Relating to the Jurisdiction of the ICAO Council Under Article II, Section 2, of the 1944 International Air Services Transit Agreement (Bahrain, Egypt and United Arab Emirates v. Qatar) - International Court of Justice (United Nations, 2022)
Appeal brought by the Kingdom of Bahrain, the Arab Republic of Egypt and the United Arab Emirates on 4 July 2018 from the Decision of the Council of the International Civil Aviation Organization, dated 29 June 2018